2019
DOI: 10.1002/jsfa.10006
|View full text |Cite
|
Sign up to set email alerts
|

Species‐dependent effect of cover cropping on trace elements and nutrients in vineyard soil and Vitis

Abstract: BACKGROUND The research focused on the evaluation of the impact of cover cropping on trace metals (Fe, Mn, Cu, Zn, Pb, Co and Cd) and nutrients in vineyard soils and Vitis vinifera L. For this purpose, two types of cover crops (Lolium perenne L. and Medicago sativa L.) and their mixture were planted between vine rows of Muscat white in the vineyard in South Crimea. Trace elements, nutrients and other parameters were analyzed in the soil layers, leaves and grapevines of control and cover cropped plots. RESULTS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Despite the potential benefits of cover cropping, there is industry resistance to incorporating grasses in the under-vine region because of perceived cover crop-vine nitrogen competition, which has been indicated in previous studies, but not assessed in mixed grass+legume cultivations (Celette et al 2009;King & Berry 2005b;Vystavna et al 2020). Not only were yields and fruit quality unaffected by the cover cropping treatments in our study, we demonstrated that the combination of grass and legume cover crops in the under-vine region represents a more valuable contribution towards the building and maintenance of OC and N in the rooting zone, where vines can access it, than legume cover crops alone.…”
Section: Discussionmentioning
confidence: 96%
“…Despite the potential benefits of cover cropping, there is industry resistance to incorporating grasses in the under-vine region because of perceived cover crop-vine nitrogen competition, which has been indicated in previous studies, but not assessed in mixed grass+legume cultivations (Celette et al 2009;King & Berry 2005b;Vystavna et al 2020). Not only were yields and fruit quality unaffected by the cover cropping treatments in our study, we demonstrated that the combination of grass and legume cover crops in the under-vine region represents a more valuable contribution towards the building and maintenance of OC and N in the rooting zone, where vines can access it, than legume cover crops alone.…”
Section: Discussionmentioning
confidence: 96%